How seed dispersal influences island plant populations.
Plants are normally anchored to one location, so depend upon a variety of both biological and non-biological agents such as animals, birds, wind and ocean currents to disperse their seeds. Patterns of seed dispersal are therefore largely determined by the dispersal mechanism, which have important implications for plant and animal populations.